KONSEP ECOTHEOLOGY DALAM TAFSIR AL-BAḤR AL-MADĪD (Penafsiran Sufistik Ibnu ‘Ajibah terhadap Ayat-ayat Berwawasan Lingkungan dalam al-Qur’an) - Abdul Rohman; Ach Khoiri Nabil; Aqib Zuhri Adi Kusuma; Muhammad Nasiruddin; Idri (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The world has recently been hit by an environmental crisis caused by human exploitation of nature. This attitude of humans stems from their denial of the sacredness of nature, which is rooted in the loss of spiritual and moral values. In addressing the issue of the environmental crisis, the researcher is interested in examining Ibn ‘Ajibah’s interpretation of ecological verses and exploring them within the discourse of ecotheology, which has been widely developed recently. This research is purely a literature study, using a multidisciplinary approach that includes thematic interpretation, theological-sufistic, and ecological approaches. The results of this research are twofold: first, based on the issue underlying this research, Ibn ‘Ajibah’s interpretation of environmental verses is classified into two themes, namely the relationship between Allah and nature, and the relationship between nature and humans. Second, the concept of ecotheology in the Tafsir al-Baḥr al-Madīd includes two main concepts, namely: the concept of nature as a divine theophany; and the concept of humans as khalīfatullāh fī al-arḍ. In conclusion, in Ibn ‘Ajibah’s interpretation, nature is a manifestation of Allah, just like humans. Therefore, humans must repair the damage to nature, preserve it, and protect it from further damage. This is an application of their role as Allah’s delegates on Earth.